Social Competence and its relationship to psychological stress among university students (A Field study at a sample students from Tishreen University( (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to know the level of social competence and the level of psychological stress, the relationship of Social Competence to  psychological stress  among a sample of first year students at Tishreen University. It also aimed to reveal the differences in the level of  Social Competence  and psychological stress  among The study sample according  to the variety of sex and residency .Social Competence scale by (Abo Rumman,2008) was used  in order to achieve the aims of the research, and psychological stress scale among university students which was designed by ( Al Hajjar and Dukhan ,2005),they were used after verifying their validity and reliability  in the current  research.  The study sample consisted of (445) male and female students from the first year students from different colleges at Tishreen University . The results of the research  showed that the level of  Social competence among the members of the   research sample was  average, as well as the level of the competence on each dimension with  average degree except for its level on the dimension compliance with laws ,which  came with a high degree. Also, the level of psychological stress of the the research sample is average on the scale as a whole and on its dimension, and high on the dimensions  dimensions( family pressure, personal pressure and social pressure. The existence of an inverse statistically correlation relationship with statistical  significance between the total scores of the research sample on the social competence scale and their total scores on the psychological stress scale except for dimension the university  environment pressure.  A statistically significant differences was found between  the mean score of the research sample on the  Social Competence scale due to gender variable in favor of males except for dimension compliance with law and authority and matters related to security and safety. A statistically significant difference was found between the mean scores of the research sample  on psychological stress scale due to the gender variable in favor of males except for  two dimensions of study pressures and the university  environment pressure .A statistically significant difference was found between the mean scores of the research sample  on the  Social Competence scale  according to the residence  variable for students from within the governorate .Also, found statistically significant differences between the mean scores of the research sample  on psychological stress scale according to the residence  variable for students in the university housing.